Absence of Detectable Precursory Deformation and Velocity Variation Before the Large Dome Collapse of July 2015 at Volcán de Colima, Mexico - Lesage, Philippe; Carrara, Alexandre; Pinel, Virginie; Arámbula-Mendoza, Raul (Frontiers in Earth Science, 2018)
Improving the ability to foresee volcanic eruption is one of the main objectives of volcanologists. For this purpose, it is essential to better detect eruption forerunners and to understand their relationship with eruptive processes. The evaluation of the performance of the forecasting methods partly relies on the estimation of the frequency of occurrence of the various precursory phenomena. Possible lack of precursor before some events must also be carefully documented and analyzed. In this study, we check for the existence of detectable precursors before the large dome collapse event of Volcán de Colima, which occurred in July 2015, leading to the emplacement of more than 10 km long Pyroclastics Density Currents and the opening of a large breach in the crater. Based on volumes of emitted magma, the 2015 eruption is the largest event recorded at Volcán de Colima since the 1913 Plinian eruption. Surface displacements in the summit cone area are quantified over the period November 2014-June 2015 based on Synthetic Aperture Radar (SAR) images acquired by Sentinel-1 satellite. Velocity variations are investigated by coda wave interferometry. Daily cross-correlation functions of seismic noise recorded at 5 broadband stations are calculated for the period January 2013 – April 2017 and apparent velocity variations are obtained by applying the stretching method. We show that no significant surface deformation can be measured by the SAR images over an area reaching 5 km from the summit, such that the volume of emitted magma cannot have been accommodated elastically in the 6 months preceding the eruption at a depth shallower than 5 km. The time series of apparent velocity variations display fluctuations of the order of 0.05 % with characteristic time shorter than one month. Sharp velocity decreases of up to 0.2 % are associated with strong regional tectonic earthquakes. However, no velocity change with amplitude larger than the noise level is observed before the July 2015 eruption. The behavior of the surface deformation and the velocity variation is consistent with the relative quiescence of the volcano-tectonic and low-frequency seismic activities observed before this large eruptive event, a situation that could be frequent in